2009
DOI: 10.1371/journal.pone.0004902
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anti-Inflammatory Agents on the Gene Expression Profile of Stimulated Human Neutrophils: Unraveling Endogenous Resolution Pathways

Abstract: Adenosine, prostaglandin E2, or increased intracellular cyclic AMP concentration each elicit potent anti-inflammatory events in human neutrophils by inhibiting functions such as phagocytosis, superoxide production, adhesion and cytokine release. However, the endogenous molecular pathways mediating these actions are poorly understood. In the present study, we examined their impact on the gene expression profile of stimulated neutrophils. Purified blood neutrophils from healthy donors were stimulated with a cock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…9 Therefore, the findings reported by Ortona et al in this issue 5 have identified vimentin/cardiolipin as a new APS-related antigen. This antigen has limited specificitybecause it is also antigenic in patients with systemic lupus erythematosus and rheumatoid arthritis.…”
Section: Marc F Hoylaerts Center For Molecular and Vascular Biology mentioning
confidence: 93%
See 4 more Smart Citations
“…9 Therefore, the findings reported by Ortona et al in this issue 5 have identified vimentin/cardiolipin as a new APS-related antigen. This antigen has limited specificitybecause it is also antigenic in patients with systemic lupus erythematosus and rheumatoid arthritis.…”
Section: Marc F Hoylaerts Center For Molecular and Vascular Biology mentioning
confidence: 93%
“…In this issue, Ortona and colleagues have shown that affinity-purified antivimentin/cardiolipin antibodies isolated from seronegative patient samples can also induce IRAK1 phosphorylation (primarily coupled to secretion of the cytokine tumor necrosis factor ␣), a phenomenon which was not observed in incubations with purified antivimentin antibodies. 5 Therefore, these experiments (1) illustrate the dependence on phospholipids for the reaction, and (2) couple vimentin via IRAK to endothelial cell activation pathways, similar to those activated via TLRs by antiphospholipid anti-␤ 2 GPI antibodies. 7 Phosphorylation of IRAK1 triggered NF-B activation leads to transcriptional activation, similar to NF-B activation upon LPS stimulation.…”
Section: Marc F Hoylaerts Center For Molecular and Vascular Biology mentioning
confidence: 93%
See 3 more Smart Citations